Boosting bifunctional oxygen electrocatalysis of graphitic C3N4 using non-covalently functionalized non-oxidized graphene aerogels as catalyst supports. Issue 29 (13th July 2022) - Kim, Jin; Tiwari, Anand P.; Choi, Myungwoo; Chen, Qiang; Lee, Jinho; Novak, Travis G.; Park, Minsu; Kim, Kisun; An, Ki-Seok; Jeon, Seokwoo
Abstract : Optimal electron transfer with the catalyst through modulation of a graphene support with non-covalent adsorbents for achieving maximized activity and stability. Abstract : The doping state of graphene can regulate electron donation and acceptance with the supported active material during electrocatalytic reactions. Effectively doping graphene is thus crucial for inducing ideal electron transfer for the desired reaction. Functionalization of graphene with non-covalent adsorbents can accurately modulate its electronic state by providing an ideal doping configuration without damaging the basal plane. Herein, graphitic carbon-nitride (g-C3 N4 ) is embedded on non-oxidized graphene aerogel (NOGA) with non-covalent adsorbents (polyvinylpyrrolidone for n-type and pyrenebutyric acid for p-type) to promote either the oxygen reduction or evolution reaction (ORR or OER). As a result, the embedded g-C3 N4 showed catalytic performance comparable to those of noble metals, such as a low overpotential of 0.79 V vs. RHE on ORR activity, or 1.42 V vs. RHE at 10 mA cm −2 on the OER, and on n-type or p-type NOGA, respectively. This work may provide insights into the design of an effective conductive support for utilizing catalysts for multifunctional purposes.